2022
DOI: 10.3847/2041-8213/ac9c63
|View full text |Cite
|
Sign up to set email alerts
|

The Luminosity Function of Tidal Disruption Flares for the ZTF-I Survey

Abstract: The high-cadence survey of the Zwicky Transient Facility (ZTF) has completely dominated the discovery of tidal disruption events (TDEs) in the past few years and resulted in the largest sample of TDEs with optical/UV light curves well sampled around their peaks, providing us an excellent opportunity to construct a peak luminosity function (LF) of tidal disruption flares (TDFs). The new construction is necessary particularly considering that the most updated LF reported in literature has been inferred from only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…This cutoff in the luminosity function arises from the direct capture radius of an SMBH and the inverse relationship between the fallback luminosity and the black hole mass-since larger SMBH masses correspond to smaller luminosities according to the fallback rate, the direct capture of stars suppresses TDEs at the low-luminosity end of the distribution. This suppression was found observationally in Lin et al (2022), but those authors attributed this cutoff to the Eddington luminosity of the black hole.…”
Section: • •mentioning
confidence: 88%
See 1 more Smart Citation
“…This cutoff in the luminosity function arises from the direct capture radius of an SMBH and the inverse relationship between the fallback luminosity and the black hole mass-since larger SMBH masses correspond to smaller luminosities according to the fallback rate, the direct capture of stars suppresses TDEs at the low-luminosity end of the distribution. This suppression was found observationally in Lin et al (2022), but those authors attributed this cutoff to the Eddington luminosity of the black hole.…”
Section: • •mentioning
confidence: 88%
“…Recent samples of TDEs have been used to constrain this function: van Velzen (2018) used a set of 12 TDEs and found that the luminosity function of TDEs in the g band was µ -  dN dL L TDE 2.6 0.2 . More recently, Lin et al (2022) used a sample of 33 TDEs from the ZTF-I survey and found µ -  dN dL L TDE 2.3 0.2 for g-band luminosities, or ∝L −2.2±0.2 in terms of the bolometric luminosity-slightly shallower than the power-law slope inferred by van Velzen (2018). Charalampopoulos et al (2022) recovered a g-band luminosity function of µ - dN dL L TDE 2.4 from a set of 30 TDEs from the ZTF catalog in Hammerstein et al (2023), andYao et al (2023) used 33 ZTF-obtained TDEs, finding that the g-band luminosity function favored ∝L −3 when modeled as a single power law, while the bolometric luminosity scaled as ∝L −2.4 .…”
Section: Introductionmentioning
confidence: 87%
“…Although only a handful of TDEs have been discovered to be faint (M g > − 18), the luminosity functions (LFs) of optical TDEs suggest that their real number should be large as all of these LFs show a rising trend toward the low end (van Velzen 2018; Lin et al 2022b;Charalampopoulos et al 2023;Yao et al 2023). However, an accurate LF profile calls for more precise constraints, particularly when discovering more faint TDEs.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the faintest TDEs discovered by the ZTF survey, AT 2023clx could provide the first data point at L g < 10 42.4 erg s −1 . We also used the "  1 max" method described in Lin et al (2022b) to estimate the volumetric rate and considered the latest TDE selection criteria from the ZTF survey (Yao et al 2023). The  max is defined as: For the survey duration (τ survey ), we set a starting date of 2018 October 1 UT and an end date of 2023 May 1 UT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation